Languages and compilers for parallel computing : 18th International Workshop, LCPC 2005, Hawthorne, NY, USA, October 20-22, 2005 : revised selected papers - Ayguade, Eduard; Baumgartner, Gerald; Ramanujam, J (Springer, 2006)
This book constitutes the thoroughly refereed post-proceedings of the 18th International Workshop on Languages and Compilers for Parallel Computing, LCPC 2005, held in Hawthorne, NY, USA in October 2005. The 26 revised full papers and 8 short papers presented were carefully selected during two rounds of reviewing and improvement. The papers are organized in topical sections on register optimization, compiling for FPGA's and network processors, model-driven and empirical optimization, parallel languages, speculative execution, run-time environments, high-productivity languages for HPC: compiler challenges, and compile-time analysis.